Operating System Development Based on Open Source Software in Online Learning Systems - Agus Prasetya; Muqorobin Muqorobin; Farid Fitriyadi (Institut Teknologi Bisnis AAS Indonesia, 2021)
Abstract—During the Covid-19 pandemic, all learning activities were carried out online. Many learning media and software are used in online learning. One of them is the Open Source Operating System which is currently widely used in online learning systems. This makes the operating system much attention by the world of education, researchers, government organizations, individuals, even large software companies such as Google and others who are very interested in developing Open Source software, especially the Linux Operating System. This makes the authors interested in knowing how to develop an operating system based on open source software in online learning systems and disseminate the use of open source software to the public.